2012
DOI: 10.1016/j.neuropharm.2011.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Gestational and postpartum corticosterone exposure to the dam affects behavioral and endocrine outcome of the offspring in a sexually-dimorphic manner

Abstract: Exposure to high levels of glucocorticoids in utero and during the postpartum period has a detrimental effect on brain development. We created an animal model of postpartum stress/depression based on administering high levels of corticosterone (CORT) to the dams during the postpartum period which caused behavioral changes and reduced hippocampal cell proliferation in the offspring. As the consequences of early exposure to glucocorticoids may depend on the dose and the developmental stage of the offspring, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 86 publications
3
42
1
Order By: Relevance
“…However, dose and species differences could account for this discrepancy, as forced swim test outcomes differ between mice and rats (Slattery and Cryan, 2012). Our results confirm previous work with this model of PPD in which maternal postpartum CORT did not significantly affect depressivelike behavior of adult offspring in the forced swim test (Brummelte et al, 2006(Brummelte et al, , 2012. Our findings show that maternal postpartum fluoxetine exerts enduring changes in serotoninrelated behavior, which may manifest from disturbances to the developing serotonin system following developmental exposure to fluoxetine.…”
Section: Maternal Postpartum Fluoxetine Increased Serotonin-mediated supporting
confidence: 80%
See 4 more Smart Citations
“…However, dose and species differences could account for this discrepancy, as forced swim test outcomes differ between mice and rats (Slattery and Cryan, 2012). Our results confirm previous work with this model of PPD in which maternal postpartum CORT did not significantly affect depressivelike behavior of adult offspring in the forced swim test (Brummelte et al, 2006(Brummelte et al, , 2012. Our findings show that maternal postpartum fluoxetine exerts enduring changes in serotoninrelated behavior, which may manifest from disturbances to the developing serotonin system following developmental exposure to fluoxetine.…”
Section: Maternal Postpartum Fluoxetine Increased Serotonin-mediated supporting
confidence: 80%
“…Previous work with using this model showed that after 1 h of restraint, maternal postpartum CORT did not significantly alter serum CORT concentrations in either adult male or female offspring (Brummelte et al, 2006(Brummelte et al, , 2012. This suggests that maternal postpartum CORT results in developmental disturbance specific to negative feedback of the HPA axis.…”
Section: Maternal Postpartum Fluoxetine Increased Serotonin-mediated mentioning
confidence: 86%
See 3 more Smart Citations